Rebuilding Trust on the Tracks: Unveiling the Crisis Strategic Communication Cycle of Brand Equity and Participatory Culture in MRT Jakarta - Desfianti, Winda Galuh; Annabel, Angela; Kusuma Patera, A. A. Aditya (Syntax Corporation, 2026)
This study investigates how participatory digital communication shapes brand equity recovery during institutional crises in public-sector transportation. In the digital era, brand equity arises from both institutional messaging and public participation. Drawing on Keller’s Customer-Based Brand Equity (CBBE) model and Jenkins’ participatory culture theory, it analyzes two 2025 MRT Jakarta disruptions: a public demonstration and QRIS payment failure. Employing a qualitative case study, the research examines social media communication, public responses, user-generated content, and media coverage across trigger, reaction, and recovery phases. Findings show MRT Jakarta’s transparent, empathetic, dialogic digital strategies turned disruptions into trust-building opportunities. Public participation—via reposting, crowdsourcing, humor, and advocacy—stabilized narratives and bolstered credibility. The study demonstrates that public-sector brand equity thrives not on operational perfection but collaborative meaning-making and digital empathy. By framing citizens as co-creators, MRT enhanced resonance and legitimacy. This extends brand equity theory to public digital governance and provides crisis communication insights for participatory media.